Ballistic extremity wounding : quantifying tissue damage associated with military firearms - Stevenson, Tom (Cranfield University, 2018)
Gunshot wounding (GSW) is often the second most common mechanism of injury after explosive in war. With a large proportion of survivors typically suffering with extremity wounds, the clinical burden is often substantial. Following the recent Iraq and Afghanistan conflicts, this work set out to ascertain the clinical burden of GSW suffered by UK military personnel. A critical literature gap uncovered was pertaining to the effect of clothing on GSW patterns. A synthetic limb model was used to test the effect of UK military clothing on GSW patterns in a maximal and minimal state, as worn by front-line service personnel, using 7.62 x 39 mm and 5.45 x 39 mm ammunition types. Further work was then undertaken to develop a technique to facilitate precise examination of GSW patterns within an opaque target. Lastly, this led to the development of a cadaveric animal limb model to test the same military clothing states as with the synthetic model. Increased damage was found in the presence of the maximal clothing state within both models, which would translate clinically into a wound requiring more extensive surgical intervention. The relevance of these findings, along with critical appraisal of each model used are then discussed, with further work proposed.